Does improved hearing result in altered inner ear morphology? - Tanja Schulz-Mirbach (Frontiers in Marine Science, 2015)
The sense of hearing plays an important role for fishes to obtain information about their (acoustic) environment (e.g. Popper 2011, Fay 2011). In numerous taxa, ancillary auditory structures like swimbladder modifications evolved, leading to an improved audition (Braun and Grande 2008). Despite a profound knowledge of inner ear diversity and ancillary auditory structures (for an overview see Schulz-Mirbach and Ladich 2015, Ladich 2015), the relationship between the morphology of these structures and hearing abilities remains to be elucidated. We tested the hypothesis that swimbladder modifications coincide with differences in inner ear morphology, using cichlids as a model because they show considerable intrafamilial diversity in swimbladder morphology and hearing capabilities (Schulz-Mirbach et al. 2012, 2014). We compared Steatocranus tinanti (vestigial swimbladder), Hemichromis guttatus (large swimbladder without extensions), and Etroplus maculatus (intimate connection between swimbladder and inner ears) by applying immunostaining together with confocal imaging for the investigation of sensory epithelia, and high-resolution, contrast enhanced microCT imaging for characterizing inner ears in 3D. Compared to S. tinanti and H. guttatus, inner ears of E. maculatus showed an enlargement of all three maculae, and a particularly large lacinia of the macula utriculi. While our analysis of orientation patterns of ciliary bundles on the three macula types using artificially flattened maculae uncovered rather similar orientation patterns of ciliary bundles, interspecific differences became apparent when illustrating the orientation patterns on the 3D models of the maculae: differences in the shape and curvature of the lacinia of the macula utriculi, and the anterior arm of the macula lagenae resulted in an altered arrangement of ciliary bundles. Our results imply that improved hearing in E. maculatus is associated not only with swimbladder modifications but also altered inner ear morphology. However, not all modifications in E. maculatus could be connected to enhanced auditory abilities, and so a potential improvement of the vestibular sense, among others, also needs to be considered. Our study highlights the value of analyzing orientation patterns of ciliary bundles in their three-dimensional position in studies of inner ear morphology and hearing physiology.